Computational Chemical Study of Pigment of Mangosteen (Garcinia mangostana) Rind Extract as Dye Compound in Dye-Sensitized Solar Cell (DSSC) - Didik Krisdiyanto; Sudarlin Sudarlin; Hikmah Supriyati (Biology, Medicine, & Natural Product Chemistry, 2021)
The electronic transition processes of α-mangostin and β-mangostin as dye compounds in DSSC and their ability to transfer electrons to semiconductors have been studied in theory. The research was carried out computationally using the NwChem application. The methods used are Density Functional Theory (DFT) for structure optimization and Time-Dependent DFT (TD-DFT) for electronic transitions. The results showed that the energy of HOMO β-mangostin was lower that it was more stable or easier to form bonds with semiconductors. Likewise, its LUMO energy is lower than α-mangostin that it is easier to inject electrons into the semiconductor. The energy difference of HOMO-LUMO β-mangostin is smaller than α-mangostin. This shows that β-mangostin is more easily excited or more efficient in exciting solar energy to convert it into electricity. This is consistent with the molecular spectra where λmaxβ-mangostin is at a higher wavelength. Orbital analysis shows electron injection of α-mangostin and β-mangostin into the semiconductor via double O atoms in each molecule. The injection is influenced by the bond length, where the bond length of α-mangostin to TiO2 is smaller than that of β-mangostin to TiO2.